Poly[[diaqua(1,10-phenanthroline-κ2N,N′)(μ3-4-sulfonatobenzene-1,2-dicarboxylato-κ4O1:O2,O2′:O4)dysprosium(III)] dihydrate] - Zhang, Kou-Lin; Lin, Jian-Guo; Ng, Seik Weng (International Union of Crystallography, 2012)
The 4-sulfophthalate trianion in the polymeric title complex, {[Dy(C 8H 3O 7S)(C 12H 8N 2)(H 2O) 2]·2H 2O} n , bridges three water/phenanthroline-coordinated Dy III atoms to form a three-dimensional network architecture. The metal atom is further chelated by a carboxylate group and is covalently bonded to a monodentate carboxylate group and to a monodentate sulfonate group in a distorted square-anti-prismatic geometry. The coordinating and the solvent water molecules are hydrogen bonded to the network. In the crystal, one solvent water molecule is disordered over two positions [major component = 59 (3)%].